Species Distribution and Susceptibility to Azoles of Vaginal Yeasts Isolated Prostitutes - Norma T. Gross; M. L. Arias; M. Moraga; Y. Baddasarow; C. Jarstrand (Hindawi Limited, 2007)
Objective. We investigated the use of miconazole among female prostitutes in Costa Rica as well as the distribution of vaginal yeasts and the susceptibility pattern to azoles of strains obtained from this population. Our intention was to relate a frequent use of miconazole to occurrence of vaginal yeasts resistant to azoles. Methods. Vaginal samples were taken from 277 patients that have previously used azoles. Vaginal swabs were obtained for direct microscopy and culture. Yeast isolates were identified by germ tube test and assimilation pattern. Susceptibility testing was determined using a tablet diffusion method. Results. The number of clinical Candida isolates (one from each patient) was 57 (20.6%). C. albicans was the predominant species (70%), followed by C. parapsilosis (12%), C. tropicalis (5.3%), C. glabrata and C. famata (3.5% each), C. krusei, C. inconspicua and C. guilliermondii (1.7% each). The majority of vaginal Candida isolates were susceptible to ketoconazole (91%), fluconazole (96.5%), and itraconazole (98%). A lower susceptibility of some isolates to miconazole (63%) was observed as compared to the other azoles tested. Moreover, the strains, nonsusceptible to miconazole, were more often obtained from patients that have used this antifungal at least four times within the last year before taking the samples as compared to those with three or less treatments (P<.01). Conclusion. An indiscriminate use of miconazole, such as that observed among female prostitutes in Costa Rica, results in a reduced susceptibility of vaginal yeasts to miconazole but not to other azoles.